THE VALIDITY OF CRYPTOCURRENCY’S ZAKAT: A study of the Mui Fatwa Number 13 of 2011 on the Law of Zakat on Unlawful Wealth - Raihanun Nisa; Chairul Fahmi; Riadhus Sholihin (JURISTA: Jurnal Hukum dan Keadilan, 2025)
The advancement of digital technology has introduced cryptocurrency as a new form of asset used in transactions and investments. The emergence of this asset raises questions among Muslims, particularly regarding the obligation of zakat. Using MUI Fatwa Number 13 of 2011 as a point of departure, this study explores the Islamic legal perspective on zakat for cryptocurrency, which discusses the prohibition of buying and selling digital currency due to elements of uncertainty and speculation. Employing a qualitative research strategy, this study adopts a normative legal framework. Data were obtained through a literature review of both classical and contemporary fiqh on zakat, as well as scholars' opinions concerning the legal status and zakat obligation on digital assets. The study finds that cryptocurrency is classified as māl (property) with an exchangeable value, and thus is subject to zakat if it meets the requirements of full ownership, nishāb, and hawl. However, since the MUI fatwa does not explicitly address zakat on such assets, further interpretation and ijtihad are necessary to fulfil the requirements of Islamic law. This study recommends that a more specific fatwa be issued regarding zakat on cryptocurrency, so that Muslim communities can have clear guidance on managing digital assets in accordance with Sharia.